On the Principle of "Unity of Knowledge and Action" in Ideological and Political Education in Universities in the New Era - Meng, Qingling (Transactions on Social Science, Education and Humanities Research, 2023)
The principle of "unity of knowledge and action" is one of the important principles of ideological and political education in colleges and universities in the new era, which has deep historical origin and rigorous scientific connotation. The application of the principle of "unity of knowledge and action" in the ideological and political education of colleges and universities in the new era is conducive to realizing the Chinese dream of the great rejuvenation of the Chinese nation; It is conducive to creating a new environment for the development of higher education. It will help train socialist builders and successors. In the new era, to learn and master the historical origin, scientific connotation and important value of the principle of "unity of knowledge and practice" in ideological and political education in colleges and universities needs to adhere to the socialist direction of running a school and create a good atmosphere of "unity of knowledge and practice"; It is necessary for teachers to firmly believe in Marxism and play the exemplary role of "unity of knowledge and practice". It is necessary for students to actively establish a high degree of consciousness and strive to be outstanding talents of "unity of knowledge and action".